Coupled modeling of land hydrology–regional climate including human carbon emission and water exploitation - Zeng, Y. (2020)
Carbon emissions and water use are two major kinds of human activities. To reveal whether these two activities can modify the hydrological cycle and climate system in China, we conducted two sets of numerical experiments using regional climate model RegCM4. Results from the first experiment revealed that near-surface air temperature may significantly increase from 2007 to 2059 at a rate exceeding 0.1 °C per decade in most areas across the country; southwestern and southeastern China also showed increasing trends in summer precipitation, with rates exceeding 10 mm per decade over the same period. These effects are believed to be caused by global warming from human carbon emissions. We incorporated a scheme of human water regulation into RegCM4 and conducted the second experiment. Model outputs showed that the groundwater table severely declined by ∼10 m in 1971–2000 through human groundwater over-exploitation in the basin; in fact, current conditions are so extreme that even reducing the pumping rate by half cannot eliminate the groundwater depletion cones observed in the area.